PERALIHAN HAK ATAS TANAH WARIS KEPADA AHLI WARIS SAAT AKAN DILAKUKAN JUAL BELI - ABDUR ROHIM (STIH Zainul Hasan Kraksaan Kraksaan, 2022)
Abstract Transfer of land rights according to positive law in Indonesia, namely property rights according to civil law. The property rights are in accordance with the provisions of the conversion in the UUPA into the transfer of land rights according to government regulations. Article 37 paragraph (1) Number 24 of 1997.Based on this, what needs to be discussed in this study is the mechanism for the transfer of land rights that can be carried out under the hands of the two bases for the transfer of land rights when buying and selling transactions are carried out under the hands can be used as evidence of the transfer of land rights according to positive law in Indonesia. This study uses a normative juridical research type using a conceptual approach to legislation. Then assisted by legal materials used, namely Primary and Secondary legal materials which are described, described, and analyzed in relation to each other.1961, especially in Article 1 of the Minister of Agrarian Regulation Number 11 of 1961 concerning the form of a deed which explains that every transfer of land rights must be made with an official deed (PPAT). Second, the transfer of land rights carried out under the hands before the enactment of PP Number. 24 of 1997 can be used as evidence of the transfer of land rights in accordance with the provisions of Article 24 concerning proof of the old rights of PP Number. 24 of 1997 concerning land registration. However, if the transfer of land rights is carried out after the enactment of government regulations Number. 24 of 1997, the transfer must be proven by the PPAT Deed. Keywords: Transfer of Inherited Land Rights